Возникновение Бельского городища - Шрамко, Б. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
SUMMARYShramko B.A. Emergence of the Belsk Site of Ancient SettlementThe paper is devoted to the study of the ancient town Belsk (Helon town) near village Belsk of the Poltava region. Problems of appearing and dating of the fortified settlment are considered. It appeared to the turn of the 8-7th century B. C. The opinion that the ancient town Belsk was founded, by the Scythians is inconvincing.